1992
DOI: 10.1093/oxfordjournals.annonc.a058252
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids in cancer prevention and therapy

Abstract: Retinoids are a class of compounds structurally related to vitamin A. In preclinical studies, all-trans retinoic acid (tretinoin), 13-cis retinoic acid (isotretinoin) and the aromatic retinoids etretinate and acitretin have preventive and therapeutic effects on carcinogen-induced premalignant and malignant lesions. Clinically, chemoprevention with isotretinoin and etretinate has been tested with some degree of success in such indications as basal cell carcinomas, squamous cell carcinomas, superficial bladder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(100 citation statements)
references
References 97 publications
3
94
0
1
Order By: Relevance
“…In HL-60 leukaemia cells all-trans-RA and 13-cis-RA were equipotent in inducing differentiation; 9-cis-RA was reported to be equipotent to 10-fold as active as all-trans-RA in inducing cell differentiation (Bollag and Holdener, 1992;Matsushima et al, 1992). Our data, on the other hand, show that 9-cis-RA is less active than all-trans-RA.…”
Section: Discussionmentioning
confidence: 41%
“…In HL-60 leukaemia cells all-trans-RA and 13-cis-RA were equipotent in inducing differentiation; 9-cis-RA was reported to be equipotent to 10-fold as active as all-trans-RA in inducing cell differentiation (Bollag and Holdener, 1992;Matsushima et al, 1992). Our data, on the other hand, show that 9-cis-RA is less active than all-trans-RA.…”
Section: Discussionmentioning
confidence: 41%
“…Recently, it has been demonstrated that ATRA may have a strong therapeutic activity in acute promyelocytic leukaemia; its mechanism primarily relates to the property of determining the maturation of the non-differentiated leukaemic promyelocytes into non-proliferating, differentiated granulocytes (Huang et al, 1988;Bollag and Holdener, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the locus for PKCoa is not within the amplicon, is again consistent with the observations in breast cancer (Keith et al, 1992) and demonstrates that the increased copy number of ERBB2, RARa and topoisomerase IIa in CALU3 is not due to aneuploidy. The RARx receptor regulates normal cellular proliferation and differentiation through activation by retinoids, (Bollag & Holdener, 1992) and can, when expressed as a fusion protein in acute promyelocytic leukaemia act as an oncogene. (Clarkson, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…(Clarkson, 1991). Gebert et al (1991) have shown the RARa gene to be expressed at high levels in CALU3 and so CALU3 may be a suitable model to study retinoids in cancer therapy, (Bollag & Holdener, 1992).…”
Section: Discussionmentioning
confidence: 99%